Effect of weight-bearing therapeutic exercise on the q-angle and muscle activity onset times of elite athletes with patellofemoral pain syndrome: a randomized controlled trial - Lee, J.; Lee, H.; Lee, W. (Journal of Physical Therapy Science, 2014)
[Purpose] The purpose of this study was to determine the effect of a weight-bearing therapeutic exercise program for elite athletes diagnosed as having patellofemoral pain syndrome (PFPS). [Subjects] The subjects were 34 elite athletes from the Seoul T Center. They were randomly allocated to three groups: an elastic band exercise group (EBG), a sling exercise group (SEG), or a control group (CG). [Methods] Therapeutic exercises were performed 3 times a week for 8 weeks. The visual analogue scale (VAS) hamstring length, and static and dynamic Q angles were used to test the exercise effect of the exercises, as well as the onset time of electromyographic activity of vastus medialis oblique (VMO) and vastus lateralis (VL). [Results] Decrease of the dynamic Q-angle in EBG was significant and significantly greater than that in CG. The decrease in VAS in SEG was significant and significantly greater than that in CG. There were significant differences in the VL and VMO activity onset times in SEG between pre- and post-test, and their differences between pre- and post-test were also significantly different. [Conclusion] Weight-bearing therapeutic exercise is hoped that clinicians will use this information for better implementation of effective exercise methods for elite athletes with PFPS.